Repeat infusion of autologous bone marrow cells in multiple sclerosis: protocol for a phase I extension study (SIAMMS-II). Issue 9 (11th September 2015) - Rice, Claire M; Marks, David I; Walsh, Peter; Kane, Nick M; Guttridge, Martin G; Redondo, Juliana; Sarkar, Pamela; Owen, Denise; Wilkins, Alastair; Scolding, Neil J
Abstract : Introduction: The 'Study of Intravenous Autologous Marrow in Multiple Sclerosis (SIAMMS)' trial was a safety and feasibility study which examined the effect of intravenous infusion of autologous bone marrow without myeloablative therapy. This trial was well tolerated and improvement was noted in the global evoked potential (GEP)—a neurophysiological secondary outcome measure recording speed of conduction in central nervous system pathways. The efficacy of intravenous delivery of autologous marrow in progressive multiple sclerosis (MS) will be examined in the phase II study the 'Assessment of Bone Marrow-Derived Cellular Therapy in Progressive Multiple Sclerosis (ACTiMuS; NCT01815632 )'. In parallel with the 'ACTiMuS' study, the current study 'SIAMMS-II' will explore the feasibility of repeated, non-myeloablative autologous bone marrow-derived cell therapy in progressive MS. Furthermore, information will be obtained regarding the persistence or otherwise of improvements in conduction in central nervous system pathways observed in the original 'SIAMMS' study and whether these can be reproduced or augmented by a second infusion of autologous bone marrow-derived cells. Methods and analysis: An open, prospective, single-centre phase I extension study. The six patients with progressive MS who participated in the 'SIAMMS' study will be invited to undergo repeat bone marrow harvest and receive an intravenous infusion of autologous, unfractionated bone marrow as a day-case procedure. The primary outcome measure is the number of adverse events, and secondary outcome measures will include change in clinical rating scales of disability, GEP and cranial MRI. Ethics and dissemination: The study has UK National Research Ethics Committee approval (13/SW/0255). Study results will be disseminated via peer-reviewed publications and conference presentations. Trial registration number: NCT01932593.